Murder games [compact disc, unabridged] : a thriller - Patterson, James, 1947-; Roughan, Howard (Murder games, 2017)
As the tabloid frenzy over a serial killer reaches a fever pitch, Elizabeth Needham and Dylan Reinhart must connect the clues to discover what the victims have in common.